2019
DOI: 10.1111/pbi.13130
|View full text |Cite
|
Sign up to set email alerts
|

PeSTZ1, a C2H2‐type zinc finger transcription factor from Populus euphratica, enhances freezing tolerance through modulation of ROS scavenging by directly regulating PeAPX2

Abstract: Summary In the present study, PeSTZ1, a cysteine‐2/histidine‐2‐type zinc finger transcription factor, was isolated from the desert poplar, Populus euphratica, which serves as a model stress adaptation system for trees. PeSTZ1 was preferentially expressed in the young stems and was significantly up‐regulated during chilling and freezing treatments. PeSTZ1 was localized to the nucleus and bound specifically to the PeAPX2 promoter. To examine the potential functions of PeSTZ1, we overexpressed it in poplar 84K hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 77 publications
(187 reference statements)
3
56
0
Order By: Relevance
“…In the initial stage of the AsA-GSH cycle, APX scavenges H 2 O 2 [ 114 ]. Previously, it has been described that APX can be positively modulated by H 2 S through persufidation [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the initial stage of the AsA-GSH cycle, APX scavenges H 2 O 2 [ 114 ]. Previously, it has been described that APX can be positively modulated by H 2 S through persufidation [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2− ), and hydroxyl radical (HO•) [25][26][27][28][29][30] as ROS signals can activate redox-responsive proteins, such as protein kinases and transcription factors, such as MAPK cascade [10], and activate of ZAT12 [31]. He et al [32] found that PeSTZ1 could enhance freezing tolerance through modulation of ROS scavenging by directly regulating PeAPX2 in Populus euphratica.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is an important abiotic factor affecting plant physiological processes [2]. Plants can endure or resist low temperature stress by accumulating internal osmotic adjustment substances including proline, betaine, and soluble sugar [3], and increasing the synthesis of metabolism-related proteins, molecular chaperones, and antifreeze proteins [4,5]. Many quantitative trait loci (QTL) and genes were found to be involved in cold tolerance in plants [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%